Using active learning in college classes: a range of options for faculty - Sutherland, Tracey E.; Bonwell, Charles C. (San francisco: Jossey-bass, 1996)
Sus temas principales son: 1.- The active learning continum chhsing activities to engage students in the classroom, 2.- Providing structure the critical element, 3.- Enhancing the lecture revitalizing a traditional format, 4.- Encouraging self-assessment writing as active learning, 5.- Using electronic tools to promote active learning, 6.- Cooperative learning making groupwork work, 7.- Emerging issues in the discussion of active learning
Keywords: Pedagogía - Evaluaciones educativas